Numerical Simulations of the Effect on Aerodynamic Performances of the Inter-propeller Distance in a Contra-rotating Propeller - H. Bentrad; H. Moulai; A. Bekhti; S. Laâzab (Journal of Applied Fluid Mechanics)
We investigate the aerodynamics of low-Reynolds-number contrarotating propellers (CRPs) through numerical simulations. This field has gained increasing relevance owing to advancements in unmanned aerial vehicle technologies. The primary objective of this study was to evaluate the effect of interpropeller distance on the aerodynamic performance of CRPs, measured using the thrust coefficient (CT ), power coefficient (Cp) , and efficiency (η). Transient three-dimensional computational fluid dynamics simulations employing the unsteady Reynolds-averaged Navier–Stokes equations coupled with the k–ε turbulence model were conducted on an isolated propeller at various advance ratios. The results were then compared with the experimental data from a similarly shaped propeller. Simulations of different CRP interpropeller distances were performed with OpenFOAM software. The results indicated that increasing the interpropeller distance significantly enhances thrust, with a corresponding slight increase in efficiency.